2020
DOI: 10.1108/vjikms-10-2019-0159
|View full text |Cite
|
Sign up to set email alerts
|

Does servant leadership affect work role performance via knowledge sharing and psychological empowerment?

Abstract: Purpose This paper aims to examine how servant leaders play an essential role in employee work role performance by assessing the mediating role of knowledge sharing and psychological empowerment. Design/methodology/approach Data was collected from a sample of 583 employees working in a public sector organization in India. Structural equation modeling has been used to test the proposed model. Findings The results contribute to new knowledge that servant leadership has a positive link to work role performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 78 publications
5
25
0
4
Order By: Relevance
“…Similarly, Kim and Park [98] also found a positive relationship between transformational leadership and knowledge sharing. Additionally, Tripathi et al [99] report similar findings to Shafi et al [100], who investigated the relationship between servant leaders and knowledge sharing and found a positive association. Some researchers have discovered, however, that leaders can operate as a barrier to knowledge sharing.…”
Section: Leadershipsupporting
confidence: 56%
“…Similarly, Kim and Park [98] also found a positive relationship between transformational leadership and knowledge sharing. Additionally, Tripathi et al [99] report similar findings to Shafi et al [100], who investigated the relationship between servant leaders and knowledge sharing and found a positive association. Some researchers have discovered, however, that leaders can operate as a barrier to knowledge sharing.…”
Section: Leadershipsupporting
confidence: 56%
“…POS, which can be interpreted as employees' perceptions of organizational care and appreciation for their contributions (Eisenberger et al 1986), had been proven to have a positive effect on knowledge sharing (Cugueró-Escofet et al 2019). On the other hand, servant leadership as a context for more minor interactions was also confirmed to positively affect knowledge sharing (Kadarusman & Bunyamin 2021, Tripathi et al 2020). Besides, previous research showed the role of organizational citizenship behavior (OCB) in the relationship between POS, servant leadership, and knowledge sharing.…”
Section: Introductionmentioning
confidence: 91%
“…It is not surprising then that many research results confirm the positive influence of knowledge sharing on public sector organizations. Knowledge sharing is thought to be positively related to individual work performance (Tripathi et al 2020), innovative work behavior (Khorakian et al 2019), and organizational innovation (Al-Husseini & Elbeltagi 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Essa sensação de estar no controle do trabalho traz inúmeros efeitos positivos, como melhoria do desempenho (Tripathi et al, 2020), cidadania organizacional (Newman et al, 2017), criatividade (X. Zhang & Bartol, 2010) e comportamento inovador (Khan et al, 2021).…”
Section: Liderança Servidora Empoderamento Psicológico E Comportamento Inovador No Trabalhounclassified
“…Em suma, a liderança servidora parece ter o potencial de influenciar positivamente o empoderamento psicológico, bem como o comportamento dos funcionários (Tripathi et al, 2020). Além disso, diversos estudos identificaram que a liderança servidora esteve positivamente associada ao empoderamento psicológico (Khan et al, 2021;Tripathi et al, 2020;Yang et al, 2019), inclusive no setor público (Allen et al, 2018). No contexto das evidências teóricas e empíricas discutidas, hipotetiza-se que:…”
Section: Liderança Servidora Empoderamento Psicológico E Comportamento Inovador No Trabalhounclassified